The prebiotic effects of omega-3 fatty acid supplementation: A six-week randomised intervention trial. (1st January 2021) - Vijay, Amrita; Astbury, Stuart; Le Roy, Caroline; Spector, Tim D; Valdes, Ana M
ABSTRACT: Prebiotics are compounds in food that benefit health via affecting the gut microbiome. Omega-3 fatty acids have been associated with differences in gut microbiome composition and are widely accepted to have health benefits, although recent large trials have been inconclusive. We carried out a 6-week dietary intervention comparing the effects of daily supplementation with 500 mg of omega-3 versus 20 g of a well-characterized prebiotic, inulin. Inulin supplementation resulted in large increases in Bifidobacterium and Lachnospiraceae. In contrast, omega-3 supplementation resulted in significant increases in Coprococcus spp . and Bacteroides spp, and significant decreases in the fatty-liver associated Collinsella spp . On the other hand, similar to the results with inulin supplementation which resulted in significant increases in butyrate, iso-valerate, and iso-butyrate ( p < .004), omega-3 supplementation resulted in significant increases in iso-butyrate and isovalerate ( p < .002) and nearly significant increases in butyrate ( p < .053). Coprococcus, which was significantly increased post-supplementation with omega-3, was found to be positively associated with iso-butyric acid (Beta (SE) = 0.69 (0.02), P = 1.4 x 10 −3 ) and negatively associated with triglyceride-rich lipoproteins such as VLDL (Beta (SE) = −0.381 (0.01), P = .001) and VLDL-TG (Beta (SE) = −0.372 (0.04), P = .001) after adjusting for confounders. Dietary omega-3 alters gut microbiome composition and some of its cardiovascular effects appear to be potentially mediated by its effect on gut microbial fermentation products indicating that it may be a prebiotic nutrient.